Impact of fertigation in capsicum (Capsicum annuum) on socio economic status of marginal farmers of Chamba, Himachal Pradesh - KAPOOR, RENU; SHARMA, ANURAG; RAINA, RAJEEV; SINGH THAKUR, KEHAR; THAKUR, MANISH (The Indian Journal of Agricultural Sciences, 2022)
Vegetables have been the backbone of agricultural economy of India. The productivity of most of vegetables in Chamba district is low due to non-adoption of improved package of practices. Therefore, efforts have been made through front line demonstrations (FLDs) to demonstrate improved production technologies to increase productivity. FLDs on fertigation with water soluble fertilizers in capsicum (Capsicum annuum L.) were conducted at different locations in Chamba district of Himachal Pradesh during 2018 and 2019. The results of demonstrations showed that farmers could increase the capsicum productivity by switching over to adoption of improved production technology. Most of the farmers who tried it were convinced with fruit yield, quality and colour. During the year 2018, average high yield obtained in demonstration was 675 q/ha with 29.81% increase over check (520 q/ha). During second year also demonstration yield was higher (806 q/ha) with 46.54% increase over check (550 q/ha). The benefit:cost ratio was also high in demonstration (8.0 and 9.4) and low in check (6.8 and 4.8). The adoption of fertigation technology in farmers’ field greatly affected the economy of the farmers of the district. Technological and extension gaps exist in the district which can be bridged by popularizing package of practices and location specific integrated approaches